Health and inequality - Dias, Pedro Rosa; O'Donnell, Owen (Research on economic inequality ;, 2013)
Economists are increasingly turning their attention to the measurement and causes of health inequality. This is in response to widespread concern that health disparities reflect social injustices but is also part of the trend away from the narrow focus on inequality in income to the more encompassing analysis of inequality in well-being. Researchers interested in the extent and causes of variation in well-being cannot but turn their analytical gaze on health inequalities. This volume contains methodological and empirical contributions from leading experts in health economics and economic inequality that add further momentum to a thriving field of research. The focus is on methods for the measurement of health inequalities (income-related, multidimensional and inequalities of opportunity) as well as the analysis of their causes. The collection is essential reading for researchers already working on health inequality and provides an immediate reconnaissance of the frontiers for those entering this exciting field.